(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes the state of the construction industry in Kyrgyzstan in 2024, with a focus on the increase in capital investments and their impact on the country’s economy. In 2024, there is a noticeable growth in investment volumes in the construction sector, which contributes to the improvement of infrastructure, including in the energy and transport sectors, as well as in residential construction. This sector continues to play a key role in the country’s GDP growth, with a share of 8.3%. The article discusses the prospects for the development of the industry, including the challenges and opportunities for increasing efficiency through the introduction of innovative technologies and attracting additional investments.